Review of statistical methodologies for the detection of parent-of-origin effects in family trio genome-wide association data with binary disease traits. - HERON, ELIZABETH (My University, 2014)
The detection of parent-of-origin effects aims to identify whether the functionality of alleles, and in turn associated phenotypic traits, depends on the parental origin of the alleles. Different parent-of-origin effects have been identified through a variety of mechanisms and a number of statistical methodologies for their detection have been proposed, in particular for genome-wide association studies (GWAS). GWAS have had limited success in explaining the heritability of many complex disorders and traits, but successful identification of parent-of-origin effects using trio (mother, father and offspring) GWAS may help shed light on this missing heritability. However, it is important to choose the most appropriate parent-of-origin test or methodology, given knowledge of the phenotype, amount of available data and the type of parent-of-origin effect(s) being considered. This review brings together the parent-of-origin detection methodologies available, comparing them in terms of power and type I error for a number of different simulated data scenarios, and finally offering guidance as to the most appropriate choice for the different scenarios.
PUBLISHED
Keywords: Genome-wide association studies imprinting maternal genetic effects mother/offspring genotype interactions; Genome-wide association studies imprinting maternal genetic effects mother/offspring genotype interactions; Genes & Society; Genetic/Molecular epidemiology; Statistical Genetics